2022
DOI: 10.1111/abac.12273
|View full text |Cite
|
Sign up to set email alerts
|

Who's Greenwashing Via the Media and What are the Consequences? Evidence From China

Abstract: We show that those Chinese listed companies that are riding high on the media corporate social responsibility (CSR) ranking lists tend to have greater advertising (sales) expenses and poor environmental performance. This observation suggests that some companies opportunistically use media to greenwash their image, hoping to capture economic rents. Indeed, our evidence shows that greenwashing firms benefit in the lending market by exploiting the media to gain a kind of environmental, social, and governance (ESG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Included studies also stressed that CSR decoupling and greenwashing are negatively related to ROA (Walker & Wan, 2012), Tobin's Q (Liu et al, 2023; Hawn & Ioannou, 2016, more pronounced by CSR intensive industries), cumulative abnormal returns (Du, 2015), and access to finance (Garcia‐Sanchez et al, 2021). Moreover, CSR decoupling lowers interest rates and collateral loans for blue and yellow, but not for green grade firms (Cao et al, 2022). However, according to Schons and Steinmeier (2006), CSR decoupling is rewarded by higher financial performance if it is directed at low‐proximity stakeholders.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Included studies also stressed that CSR decoupling and greenwashing are negatively related to ROA (Walker & Wan, 2012), Tobin's Q (Liu et al, 2023; Hawn & Ioannou, 2016, more pronounced by CSR intensive industries), cumulative abnormal returns (Du, 2015), and access to finance (Garcia‐Sanchez et al, 2021). Moreover, CSR decoupling lowers interest rates and collateral loans for blue and yellow, but not for green grade firms (Cao et al, 2022). However, according to Schons and Steinmeier (2006), CSR decoupling is rewarded by higher financial performance if it is directed at low‐proximity stakeholders.…”
Section: Resultsmentioning
confidence: 99%
“…Du (2015) used the Chinese greenwashing list, published by the South Weekend newspaper. According to Cao et al (2022), the simultaneous firm inclusion in the CSR media list (China Research Center) and the inclusion of environmental credit evaluations as blue and yellow grades indicate greenwashing behavior. Based on manual content analyses, Wang et al (2023) and Walker and Wan (2012) differentiated between symbolic (qualitative) and substantive (quantitative) descriptions within the environmental report.…”
Section: Research Framework and Included Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to research, there is a higher probability for individuals or organizations to participate in the misrepresentation of environmentally friendly practices and the dissemination of inaccurate ESG information, leading to the manifestation of ESG greenwashing behavior [ 56 ]. Companies that engage in greenwashing also leverage media channels to enhance their reputation and gain support for their environmental, social, and governance (ESG) initiatives [ 57 ]. According to research, corporations that effectively handle and reveal data regarding environmental, social, and governance (ESG) concerns tend to enjoy a more favorable public image [ 58 ].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In essence, "greenwashing" refers to a corporate strategy of projecting a socially responsible image while doing nothing to actually implement it [33,[35][36][37]. The various economic consequences of corporate "greenwashing" behavior have been extensively investigated in previous studies, including negative market reactions [38][39][40], reduced/no impact on financial performance [36,41,42], reduced audit fees [43], and benefits in the loan market [44]. Li additionally found that cheap talk on environmental responsibility led to a decrease in the number of securities analysts who released forecasts, a rise in the divergence of earnings forecasts, and a decline in the forecast accuracy of analysts with a poor reputation [10].…”
Section: The Economic Consequences Of "Greenwashing" and "Brownwashin...mentioning
confidence: 99%